The Pass-Through of Exchange Rate in the Context of the European Sovereign Debt Crisis - Nidhaleddine Ben Cheikh; Christophe Rault (Institute for the Study of Labor (IZA), 2015)
This paper investigates whether exchange rate pass-through (ERPT) into import prices is a nonlinear phenomenon for five heavily indebted Euro area countries, namely the so-called GIIPS group (Greece, Ireland, Italy, Portugal, and Spain). Using logistic smooth transition models, we explore the existence of nonlinearity with respect to sovereign bond yield spreads (versus the German bund) as an indicator of confidence crisis/macroeconomic instability. Our results provide strong evidence that the extent of ERPT is higher in periods of macroeconomic distress, i.e. when sovereign bond yield spreads exceed a given threshold. For almost all the GIIPS countries, we reveal that the increase in macroeconomic instability and the loss of confidence during the recent sovereign debt crisis has entailed higher sensitivity of import prices to exchange rate movements. For instance, the rate of pass-through in Greece is equal to 0.66% when the yield differential is below 2.13%, but beyond this threshold level, the sensitivity of import prices becomes higher and reaches full ERPT. Our findings raise the serious question of whether the exchange rate could be an effective tool to boost the trade balance and prevent deflationary threats when financial crisis hits.
Keywords: C22; E31; F31; 330; exchange rate pass-through; import prices; sovereign spreads; smooth transition models